Anti-Bourgeois for What? - Jeremy Gilbert (Media Theory, 2020)
This short commentary responds to Gary Hall’s programatic critical provocation ‘Anti-Bourgeois Theory’. It points to some of the issues involved in understanding the politics of French ‘theory’ when detached from its historical context, and invites reflection on the resonances between Hall’s positions and those of some key thinkers in the Marxist tradition.